Prevalence and S gene characterization of porcine epidemic diarrhea virus in Sichuan province, China (2023–2024) - Xiao, Lu; Kang, Run-min; Wu, Xue-jing; Yu, Ji-feng; Yang, Jun-yan; Mao, Cong-jian; Xie, Jing; Ye, Yong-gang; Li, Xing-yu; Wei, Yong; Zeng, Zi-xuan; Kang, Wei-li; et al. (Frontiers in Veterinary Science, 2026)
Porcine epidemic diarrhea virus (PEDV) is a major cause of devastating economic losses in the global swine industry. Sichuan Province, a major swine-producing region in China, is therefore a critical area for monitoring PEDV prevalence and evolution. We analyzed clinical samples collected from 365 diarrheic piglets across 70 pig farms located in 20 regions of Sichuan Province, China, from 2023 to 2024. The overall PEDV positivity rate was 40.27% (147/365). Prevalence varied considerably among regions, ranging from 0 to 63.64%, with over half (16/20) exceeding a 30% positivity rate, indicating widespread but heterogeneous circulation. Phylogenetic analyses based on the S gene from 33 representative strains revealed that they clustered into the G2b, G1c, and G2a subtypes, and these 33 PEDV S genes exhibited 94.3–99.9% nucleotide and 93.2–99.8% amino acid homology. The prevalent strains harbored frequent mutations in key antigenic sites of the S gene, including S10, SS6, and the collagenase equivalent (COE) domain. This study provides novel insights into the current epidemiology and genetic evolution of PEDV in China, which will inform more effective prevention and control strategies. Therefore, the control of the predominant G2b subtype should not be overlooked.